If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 11 = 75 Reorder the terms: 11 + 4y = 75 Solving 11 + 4y = 75 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 4y = 75 + -11 Combine like terms: 11 + -11 = 0 0 + 4y = 75 + -11 4y = 75 + -11 Combine like terms: 75 + -11 = 64 4y = 64 Divide each side by '4'. y = 16 Simplifying y = 16
| 1/2d-5-1/4d=10 | | y=-0.25*-6-0.75 | | (9-u)(5u+2)=0 | | f(x)=7x^3-4x^2 | | F(x)=7-3x-x^2 | | 2(k+21)=62 | | 90=5v-10 | | y=0.7*-18-12 | | 2j^2+13j-45=0 | | (49x)+(52y)=16200 | | 11-3x=7-1x | | 6(8+2x)=108 | | 4.2d-1.7-2.2d+4.3d+4.3=-1.4 | | 2p^2-4p-28=0 | | 2x-11=3x+9 | | x+10=110-4y | | 4ln(w)+6=12 | | 8/3-y=6 | | 10x^2+9y^2=19xy | | 3(x)=-4x-8 | | 3d+5=d-10 | | (2x+5)(3x-9)=0 | | y=-5*3/15-7 | | G(x)=-4x-8 | | 3x+x=2x+11 | | -5(2s+3)= | | 3v-10=26 | | 2x=60+x | | 30v=-42 | | f/3=2.3 | | 1x-52=-x+90 | | 5(6x+20)+4(3x-16)=330 |